Emergency Medical Services in Poland during mass events and disasters - competence and challenges. - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Czerski, Robert; Lasota, Dorota (Journal of Education, Health and Sport, 2018)
Disasters are unusual conditions, exceed the limits of normal human activity, in a moment the storm infrastructure, equipment, bring chaos and panic. In cases of mass accidents and disasters becomes a necessity to organize proper medical aid. With each passing second after the accident reduced the chances of effective assistance. Increasing the danger of loss of life by the victim or injuries leading to disability. Saving lives and health in the state of immediate threat, regardless of the reasons and circumstances require, inter alia, the proper functioning of medical staff working in the rescue system. The paper presents procedure for emergency medical services during mass events.